FAHR’S DISEASE: A CASE REPORT - Goling II, Arobe Shiek (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Fahr's Disease is a rare degenerative disorder characterized clinically by multiple neurological and psychiatric symptoms including cognitive impairment, movement disorders and seizure. It is due to abnormal deposition of calcium in areas of the brain parenchyma that control movement, including the basal ganglia and the cerebral cortex. It is a rare disorder with a documented prevalence of <1/1,000,000, with a higher incidence reported among males and a typical age of onset in the 3rd and 5th decade of life. We present the case of two females, age 19 and 43 years, who presented with generalized tonic-clonic seizures. Plain cranial CT scans both revealed bilateral calcifications in the brain parenchyma, including basal ganglia, corona radiata, gray-white matter junction and cerebellar folia. There were no masses, infarcts or hemorrhages. The patients were treated with calcium, calcitriol and anti-convulsant and advised regular follow-up.